Dry-Machining of Aerogel Foams, CH Foams, and Specially Engineered Foams Using Turn-Milling Techniques. (17th February 2018) - Randolph, Randall B.; Oertel, John A.; Cardenas, Tana; Hamilton, Christopher E.; Schmidt, Derek W.; Patterson, Brian M.; Fierro, Franklin; Capelli, Deanna
Abstract: A new method has been developed to dry-machine foams. Most of these foams are at the lower end of what is considered machineable because of their density or foam composition. Excluding aerogel foams, the foams traditionally required a wax-fill process before surviving any machining forces. This new dry-machining method uses a technique called turn-milling and replaces the old wax-fill method that added several weeks to the fabrication schedule and uncertainty in the quality of the final part. The new method utilizes a computer numerical control gang-tool–style lathe that is set up with electric live-tooling spindles. The foams are dry-machined with the lathe main spindle turning in the opposite direction of the live-tooling spindle. This turn-milling technique reduces tool pressure and can accommodate heavier roughing cuts that produce much faster cycle times. With this new dry-machining method we are able to machine the entire foam target component in one operation, eliminating the need for another machining operation for finishing the backside.